IMPLEMENTASI PAPERLESS OFFICE SYSTEM DALAM MENINGKATKAN EFEKTIVITAS KERJA (Studi Kasus : Kantor Balai Kota Way Khilau) - Rini Nurlistiani (Institut Informatika dan Bisnis Darmajaya, 2023)
Village government is the smallest scope within the Government of the Republic of Indonesia. However, the Village Government has a fairly large role in development. The office administration in the village hall is also very influential in increasing work effectiveness, one of which is in the Java City Village Hall, Kec. Way Khilau. It is hoped that paperless office administration introduced to the public will be able to increase work effectiveness and influence HR performance with the use of information technology. The service methods used include observing village officials, socializing the introduction of paperless offices, and training on how to use paperless offices properly. The result of this service is the human resources in the District Village Hall. Way Khilau is able to implement paperless information technology quite well.